The Relationship Between Social Function and Somatic Symptoms with the Quality of Life of the Elderly in the Tresna Werdha Social Home - Sulaksono, Ari Dwi; Niken Asih Laras Ati; Heri Suroso (Jurnal Kesehatan dan Kedokteran, 2025)
Social functioning and somatic symptoms are crucial components of the health status of the elderly that can influence their quality of life, particularly for those residing in social care facilities. This study aims to analyze the relationship between social functioning and somatic symptoms with the quality of life of the elderly in the Tresna Werdha Social Care Center (PSTW). The research design employed is cross-sectional, involving 146 elderly participants selected through simple random sampling from two PSTWs in East Java. The instruments used include the General Health Questionnaire (GHQ-28) to measure social functioning and somatic symptoms, as well as the Older People's Quality of Life Brief Questionnaire (OPQoL-Brief) to assess quality of life. The results indicate that the majority of the elderly have a moderate level of social functioning (63%) and experience mild to moderate somatic symptoms (58%). Spearman's test reveals a significant relationship between social functioning and quality of life (p=0.001; r=0.512), as well as between somatic symptoms and quality of life (p=0.003; r=-0.474). Thus, it can be concluded that better social functioning is associated with higher quality of life, while more severe somatic symptoms are linked to lower quality of life. This study highlights the necessity for nursing interventions focused on enhancing social interactions and managing somatic complaints among the elderly to improve their quality of life in institutional settings